Solar Energy Harvesting on S- and N-doped nanoporous Carbons - Bandosz, Teresa J. (My University, 2015)
Nowadays heteroatom-containing carbonaceous materials such as graphene or CNT have gained more and more attention of the scientists searching for inexpensive substitutes of the catalysts for energy related applications such an oxygen reduction reactions. Discovery of graphene and an extensive characterization of its electronic properties caused that the surface of traditional activated carbon has been viewed from other, unexplored before, angles. The main advantage of activated or nanoporous carbons, within the family of carbonaceous materials, is their porosity where the confined pore space effect can be utilized. Recently we have shown that specific nanoporous carbons obtained from commodity polymers can catalyze oxygen evolution reactions1, oxygen reduction reaction2 and exhibit photoluminescence properties3. This behavior was attributed to the specificity of surface microstructure, texture, and chemistry. It was found that the carbons obtained at relatively low temperature (800 oC) contain 10 nm graphic units enhancing their DC conductivity. They have also rich surface chemistry based on sulfur, nitrogen and oxygen containing groups. Even though small sp2 clusters should be important to affect the width of the band gap, the sulfur and nitrogen containing groups are hypothesized to act as chromophores/antenna accepting visible light energy. Electron deficiency on them promotes water splitting in small pores. These groups also change the electronic structure of the carbons surface and bring some level hydrophobicity to it. These features were found as important for oxygen reduction reactions4. These reactions enhance the performance of carbons as supercapcitors when the process takes place in the visible light5. References 1. Ania, C.O.; Seredych, M.; Rodriguez-Castellon, E.; Bandosz, T.J. Visible light driven photoelectrochemical water splitting on metal free nanoporous carbon promoted by chromophoric functional groups. Carbon 79 (2014) 432–441. 2. Seredych, M.; Idrobo, J-C.; Bandosz, T.J. Effect of confined space reduction of graphite oxide followed by sulfur doping on oxygen reduction reaction in neutral electrolyte. J. Mater. Chem. A. 1 (2013) 7059-7067. 3. Bandosz, T.J.; Rodriguez-Castellon, E.; Montenegro J.M.; Seredych, M. Photoluminescence of nanoporous carbons: Opening a new application route for old materials.. Carbon 77 (2014) 651–659. 4. Confined space reduced graphite oxide doped with sulfur as metal-free oxygen reduction catalyst. Seredych, M.; Rodriguez-Castellon, E.; Bandosz, T.J. Carbon 66 (2014) 227-233. 5. Seredych, M.; Rodriguez-Castellon, E.; Biggs, MJ. Skinner, W.l Bandosz, T.J. Effect of visible light and electrode wetting on the capacitive performance of S- and N-doped nanoporous carbons: Importance of surface chemistry. Carbon 78 (2014) 540–558.
Keywords: Materiales compuestos de carbono; Carbons; Supercapcitors; Graphene